HUBUNGAN TEKNIK MENERAN DENGAN KEJADIAN RUPTUR PERINEUM PADA PRIMIGRAVIDA DI POLINDES SAYANG IBU (Kecamatan Dawar Blandong Mojokerto) - Evi Yunita Nugrahini; Susilorini .; Amalia Puspita Sari (Poltekkes Kemenkes Surabaya, 2016)
Rupture of the perineum is still a problem, because there are many maternal primigravid obtained by perineal rupture caused by various factors, one of them is a straining technique. Based on preliminary studies conducted in Polindes Sayang Ibu kecamatan Dawar Blandong Mojokerto of 50 primigravida who labor, 60% experienced a rupture perineum with wrong staining technical factors. Given these problems it will be examined staining technical relationship with rupture of the perineum in primigravida.The method used is analitk with cross sectional approach with population of 30 maternity primigravida delivered in Polindes Sayang Ibu kecamatan Dawar Blandong Mojokerto at the time that the research conducted in March-July with a sample of 28 maternal primigravida. Concecutive sampling technique used by counting all the existing number of samples. The independent variable of this study is straining technique and the dependent variable in this study is the rupture of the perineum. Collecting data using observation sheets, then analyzed and statistically tested by chi-square test with significance level = 0.05.The results showed that of the 28 maternal primigravid obtained the majority (57%) do straining technique properly and most (57.2%) also maternal primigravid ruptured perineum. Data analysis was performed with chi-square test of SPSS result of count = 10.22 using a significance level (α) = 5% (0.05), df = 1 Found a critical point ( table ) = 3.84 in order to obtain count (10.22) table (3.84), then H1 is acceptedThe conclusion from the above results there is a correlation staining technique to rupture perineum in Polindes Sayang Ibu kecamatan Dawar Blandong Mojokerto. It is therefore expected health workers can provide counseling about the manner of delivery with the correct straining techniques and delivery complications, so primigravida could do straining technique right at the birth took place. Keywords: Straining technique, Rupture of the perineum.